2019
DOI: 10.1016/j.jvir.2019.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Parameters Influencing the Vascular Structure Displacement in Fusion Imaging during Endovascular Aneurysm Repair

Abstract: Purpose. To quantify the displacement of the vascular structures after insertion of stiff devices during endovascular aneurysm repair (EVAR) of abdominal aortic aneurysm, and to identify potential parameters influencing this displacement. Materials and Methods. A total of 50 patients from a single center undergoing EVAR were prospectively enrolled between January 2016 and December 2017. Fusion imaging was employed using the EndoNaut® (Therenva, France) station through a 3D/2D technology synchronizing the 3D CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In particular, Breininger et al [13] showed its accuracy by manually segmenting 2D images and fusing them with preoperative 3D CTA. Further work by Lalys et al [29] set out to quantify vascular displacement after stiff wire insertion via a pre-op 3D reconstruction and 2D intra-operative fluoroscopic imaging. Significant displacement was picked up by the fusion imaging, with a mean error of 4.1 ± 2.4 mm at the level of the renal arteries.…”
Section: Vascular Displacement After Stiff Wirementioning
confidence: 99%
“…In particular, Breininger et al [13] showed its accuracy by manually segmenting 2D images and fusing them with preoperative 3D CTA. Further work by Lalys et al [29] set out to quantify vascular displacement after stiff wire insertion via a pre-op 3D reconstruction and 2D intra-operative fluoroscopic imaging. Significant displacement was picked up by the fusion imaging, with a mean error of 4.1 ± 2.4 mm at the level of the renal arteries.…”
Section: Vascular Displacement After Stiff Wirementioning
confidence: 99%
“…3D-3D registration was superior to 2D-3D registration regarding both the spread of values and the quality of agreement of several millimeters may be acceptable for utilization during endovascular therapy of peripheral arteries, complex endovascular procedures, such as fenestrated or branched endovascular aneurysm repair (EVAR), and visceral artery revascularization, carry a higher risk of potentially fatal complications. Lalys and colleagues suggested a clinically acceptable deviation of 3 mm for an EVAR procedure based on the mean size of the renal artery ostium of 6 mm (Lalys et al 2019), which has been adopted by other authors (Schulz et al 2016;Schulz et al 2019;Lalys et al 2019). Schulz and colleagues compared both fusion techniques on CT data sets in EVAR procedures on 50 patients using the craniocaudal deviation to the lower renal artery ostium.…”
Section: Table 1 Comparison Of Different Registration Techniques and Imaging Modalitiesmentioning
confidence: 99%
“…In detail, they have reported an intra-operative displacement mostly in a cranial direction for the aortic bifurcation and in a ventral direction for the iliac one. Lalys et al (2019) evaluated how these deformations affects the fusion accuracy and they estimated a mean displacement error of 4.1 ± 2.4 mm at the level of the renal arteries. Moreover, they reported a correlation between the aortic neck angle and the fusion accuracy.…”
Section: Introductionmentioning
confidence: 99%